147k views
5 votes
Simplify x/2*x² – 2x – 24/4*8/x +4

Simplify x/2*x² – 2x – 24/4*8/x +4-example-1

1 Answer

2 votes

Answer:


(x)/(2) . \frac{ {x}^(2) - 2x - 24 }{4} . (8)/(x + 4)


= (x)/(2) . \frac{ {x}^(2) - 6x + 4x - 24x }{4} . (8)/(x + 4)


= (x)/(2) . (x(x - 6) + 4(x - 6))/(4) . (8)/(x + 4)


= (x)/(2) . ((x - 6)(x + 4))/(4) . (8)/(x + 4)


= x(x - 6)


= {x}^(2) - 6x

User Ricks
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.